The digital transformation roadmap rebuild your organization for continuous change - Rogers, David L. 1970- (Ascent Audio, 2023)
Today, every business is talking about digital transformation. With the acceleration of new technologies, every organization knows it must adapt to survive. But by their own admission, 70 percent of businesses are failing to transform. Across industries, established companies are held back by bureaucracy, inertia, and old ways of working. How can businesses break through to drive real change? The Digital Transformation Roadmap provides every leader with the answer. Acclaimed author and C-suite advisor David L. Rogers argues that businesses must transform not just products and business models-they must transform the organization itself. Based on two decades of research and advising companies around the world, Rogers identifies the five biggest barriers to digital transformation: vision, priorities, experimentation, governance, and capabilities. He then shows how any business can evolve by heeding the lessons of companies such as Disney, Walmart, Mastercard, Air Liquide, and the New York Times Company. The Digital Transformation Roadmap provides a practical blueprint for organizational change, illustrated with real-world case studies and step-by-step planning tools. Rogers shows every leader how to think beyond the churn of new technologies and rebuild their organization for a world of constant change.
Online resource; title from title details screen (O'Reilly, viewed October 3, 2023)
Keywords: Technological innovations -- Management; Information technology -- Management; New products; Strategic planning; Innovations; Gestion; Technologie de l'information; Gestion; Planification stratégique; Information technology; Management; Technological innovations; Management; Audiobooks; Livres audio